Molecular landscape of acral melanoma: an integrative review - Jesús José André Quintana Castillo; Wagner Silva; Denise Barcelos; Gilles Landman (Surgical and Experimental Pathology)
Abstract Melanoma is an aggressive malignant neoplasm and a significant public health concern due to its high mortality rate. The acral subtype—which includes acral lentiginous and subungual melanomas—exhibits distinct and complex features that differentiate it from other melanoma subtypes. Understanding its molecular profile is essential for the development of personalized therapeutic strategies. An integrative literature review enables the synthesis and critical analysis of findings from multiple studies, and within the context of acral melanoma molecular biology, it offers a foundation for generating new hypotheses and therapeutic approaches. This study employed an integrative literature review, characterized by an exploratory and descriptive methodology focused on the molecular biology of acral melanoma. Articles were collected from the MEDLINE and EMBASE databases, restricted to publications in journals ranked B2 or higher in the Qualis classification system, covering the period from January 2014 to December 2023. Defined inclusion and exclusion criteria were applied, and the methodological quality of the 38 selected articles was validated. Regarding genomic alterations, driver mutations in BRAF and NRAS were observed at lower frequencies compared to other cutaneous melanoma types. The review also addressed genetic progression, emphasizing the role of signaling pathways and chromosomal instability, including events such as focal amplifications and structural rearrangements.